Anthropocene, the plastic age and future perspectives - Porta, Raffaele (FEBS open bio, 2021)
The issue of plastic waste is one of the main topics on the international societal and political agenda since ever‐increasing growth in the quantity of plastic materials produced has gone beyond the ability to manage them effectively at their end‐of‐life. Mostly pushed by social campaigns, an ever‐increasing number of initiatives have been taken by different institutions to reduce the huge amount of plastic waste: first of all, specific legal regulations have been introduced, both to realize effective systems of plastic collection, reuse and recycling, and to outlaw the use of unnecessary disposable one‐use items. However, due to the indisputable advantages derived from the use of such a material, every action of decision makers to limit the production or use of plastics is unavoidably affected by economic evaluations, as well as by the deficiency or drawbacks of alternative materials, rather than by environmental reasons. In the three reviews in this Special ‘In the Limelight’ section, Oliver Bajt, Paola Fabbri et al. and Frederic Debeaufort – invited speakers at the Special Session on Science & Society, entitled ‘Plastics: revolution, pollution and substitution’, of the 45th FEBS Congress to be held in Ljubljana, Slovenia, on 3–8 July 2021 – describe in detail the consequences of plastic pollution (Bajt, 2021, FEBS Open Bio 11, 954‐966), the complex transition to bioplastics (Degli Esposti et al., 2021, FEBS Open Bio 11, 967‐983) and the possibility to obtain these innovative biodegradable materials from food and marine waste (Debeaufort 2021, FEBS Open Bio 11, 984‐998), respectively. This introductory commentary highlights that, in the frame of the bioeconomy paradigm, not only multidisciplinary but also inter‐ and transdisciplinary research with integrated and multifaceted approaches are needed to produce novel eco‐friendly materials with features similar to those of traditional plastics, as well as with acceptable economic and environmental impact. In the frame of the bioeconomy paradigm, inter‐ and transdisciplinary research with integrated and multifaceted approaches are needed to produce novel eco‐friendly materials with features similar to those of traditional plastics, as well as with acceptable economic and environmental impact. The bioplastics circular bioeconomy is defined as an economy where the basic building blocks for materials must derive from renewable biological resources.